CREDIT RISK MINIMIZATION WAYS AND PRICING OF BANKING SERVICES - V. E. Gladkova (Модернизация, инновация, развитие, 2016)
Accurate accounting of own expenses on rendering banking services and forming reasonable prices for them make it possible for commercial banks to adequately react to market situation changes. Credit risk minimization comprises: credit rationing (in Russia according to RF Central Bank norms); credit diversification; credit structuring; and forming reserves to cover respective bank risks (also in accordance with RF CB documents). Effective is bank credit hedging (insuring) through credit derivatives. Most advanced at international finance markets are such risk minimization systems as Basel-II and IRBA. Pricing models based on individual assessment of each borrower’s risk class (Risk Based Pricing approach) are widely used.